Arecoline is cytotoxic for human endothelial cells. (25th April 2014) - Ullah, Mafaz; Cox, Stephen; Kelly, Elizabeth; Boadle, Ross; Zoellner, Hans
<x xml:space="preserve">Abstract</x> Background Oral submucous fibrosis is a pre‐malignant fibrotic condition caused by areca nut use and involves reduced mucosal vascularity. Arecoline is the principal areca nut alkaloid and is cytotoxic for epithelium and fibroblasts. Endothelial cell cycle arrest is reported on exposure to arecoline, as is cytotoxicity for endothelial–lung carcinoma hybrid cells. We here describe cytotoxicity for primary human endothelial cultures from seven separate donors. Materials and methods Human umbilical vein endothelial cells were exposed to increasing concentrations of arecoline and examined by: phase‐contrast microscopy, haemocytometer counts, transmission electron microscopy, lactate dehydrogenase release and the methyl‐thiazol‐tetrazolium assay. Results Vacuolation and detachment of endothelium were observed at and above arecoline concentrations of 333 μg/ml or more. Ultrastructural features of cellular stress were seen after 24‐h treatment with 111 μg/ml arecoline and included reduced ribosomal studding of endoplasmic reticulum, increased autophagolysosomal structures, increased vacuolation and reduced mitochondrial cristae with slight swelling. Similar changes were seen at 4 h with arecoline at 333 μg/ml or above, but with more severe mitochondrial changes including increased electron density of mitochondrial matrix and greater cristal swelling, while by 24 h, these cells were frankly necrotic. Haemocytometer counts were paralleled by both lactate dehydrogenase release and the methyl‐thiazol‐tetrazolium assays. Conclusions Arecoline is cytotoxic via necrosis for endothelium, while biochemical assays indicate no appreciable cellular leakage before death and detachment, as well as no clear effect on mitochondrial function in viable cells. Arecoline toxicity may thus contribute to reduced vascularity in oral submucous fibrosis.